A Multi‐electrochemical Competitive Immunosensor for Sensitive Cocaine Determination in Biological Samples. Issue 4 (14th October 2015) - Vidal, Juan C.; Bertolín, Juan R.; Bonel, Laura; Asturias, Laura; Arcos‐Martínez, M. Julia; Castillo, Juan R.
Abstract: A multi‐electrochemical competitive immunosensor for the rapid determination of unmetabolized cocaine (COC) in urine, saliva and human serum matrices is reported. Anti‐cocaine polyclonal antibodies were immobilized in an oriented way onto protein‐G functionalized magnetic beads. The immunosensor is based on an array of eight carbon‐based screen‐printed electrodes for simultaneous electrochemical determinations. The treatments of the biological samples were simplified and optimized for avoiding matrix interferences. The immunosensor was sensitive ( EC50 ≈2.92–3.88 ng mL −1 COC), required a very small volume of sample (200 µL), was reproducible (%RSD was lesser than about 18 %), and accurate (recovery percentages ranged 88–117 %). Abstract :